Morphological characteristics and power output in professional road cyclists during the competition phase - Lewandowski Andrzej; Kowalewski Marcin; Kowalik Tomasz; Piekorz Zuzanna (Sciendo, 2018)
Study aim: The purpose of this study was to investigate changes in the power output and major morphological characteristics during the competition phase. We hypothesised that substantial overloads occurring during this stage cause a decrease in body mass, fat and power output levels in the cyclists.